ACCESSORY MINERALS IN PHOSPHORITES OF THE LESSER KARATAU AS AN INDICATOR OF PROVENANCE COMPOSITION - Litvinova T.V. (My University, 2004)
Issue of determination of the provenance composition based on accessory minerals in the Lesser Karatau phosphate-bearing basin is considered. Detailed lithological studies revealed six types of phosphate-bearing sections with specific composition and genetic affinity of accessory minerals. Vertical and lateral distributions of these minerals are shown for both individual deposits and the entire paleobasin. Data on the composition, genesis, and distribution of accessory minerals in phosphorites of the Lesser Karatau are used to determine the composition of ancient provenance.